2020
DOI: 10.1177/0145561320942679
|View full text |Cite
|
Sign up to set email alerts
|

CT Diagnosis of the Fracture of Anterior Nasal Spine

Abstract: Objective: To study anterior nasal spine fractures, including the incidence, missed diagnosis rates, and relationship with shapes using computed tomography (CT). Methods: Two hundred cases of axial CT images performed for maxillofacial trauma were reviewed. The incidence, correct, and missed diagnosis rates of anterior nasal spine fractures were studied. The relationship between the fracture and the shape of the anterior nasal spine was also analyzed. Results: The rate of anterior nasal spine fractures was 22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Although the anterior nasal spine (ANS) is an important anatomic marker of the maxilla, in some patients the ANS is absent or too prominent. 32 As such, the previous CAE 3D measurement method, which uses ANS as a reference point to determine the upper margin of the cleft, cannot be used in this group of patients. In contrast, the modified subtraction method can account for abnormal ANS positioning, taking the lowermost points of the inferior margins of the piriform aperture as the upper bound on the 3D virtual mask.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the anterior nasal spine (ANS) is an important anatomic marker of the maxilla, in some patients the ANS is absent or too prominent. 32 As such, the previous CAE 3D measurement method, which uses ANS as a reference point to determine the upper margin of the cleft, cannot be used in this group of patients. In contrast, the modified subtraction method can account for abnormal ANS positioning, taking the lowermost points of the inferior margins of the piriform aperture as the upper bound on the 3D virtual mask.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the modified subtraction method has wide applicability. Although the anterior nasal spine (ANS) is an important anatomic marker of the maxilla, in some patients the ANS is absent or too prominent 32. As such, the previous CAE 3D measurement method, which uses ANS as a reference point to determine the upper margin of the cleft, cannot be used in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the 22 mm peak, most of the images were observed to manifest a continuous palatal plate full of cortical bone, as was indicated by 2 times the CBT value of the 20 mm height. You et al [24] classified the morphology of the ANS region into four categories (double rod, single rod, triangular, and irregular) based on 1000 pieces of transverse CT samples, which is a perfect illustration of the anatomic variations in ANS morphology. The trend could be attributed to the anatomical variations in the ANS, such as in an irregular phenotype in which the loss of ANS prominence may result in a dramatic decrease at 24 mm.…”
Section: Discussionmentioning
confidence: 99%
“…You et al [7] recently reported that the rate of ANS fracture is 22% and that the diagnosis was missed in 95% of 200 cases of axial CT images performed for maxillofacial trauma in a single hospital.…”
Section: Discussionmentioning
confidence: 99%
“… 1 4 5 6 On the other hand, the actual incidence of ANS fracture may not be as low as predicted. You et al 7 recently reported that the rate of ANS fracture is 22% and that the diagnosis was missed in 95% of 200 cases of axial CT images performed for maxillofacial trauma in a single hospital.…”
Section: Discussionmentioning
confidence: 99%